Carcass Characteristics of West African Dwarf goats under extensive system - Mourad, M.; Gbananou, G.; Balde, I.B. (Elsevier, 2001)
Carcass characteristics of 117 West African dwarf goat kids (26 males, 29 wethers and 62 females) raised under an extensive system on the plateau of Sankaran, Faranah, Guinea were evaluated. Goats, 12–18 months of age were slaughtered at body weights of 14.5, 19.1 and 19.9 kg, respectively. At a constant body weight, the carcass length was longer (P